What Do We Know About Business Families? Setting the Stage for Leveraging Family Science Theories. (March 2020) - Combs, James G.; Shanine, Kristen K.; Burrows, Sarah; Allen, Jared S.; Pounds, Troy W.
Researchers recently pointed to family science as one avenue for better understanding business families. We submit, however, that leveraging family science will require building on what researchers have already learned, often without the benefit of family science theories. Thus, we review progress from studies that investigate links between business family attributes and family firms and integrate our review with descriptions of family science theories that pertain to each attribute. By pairing what is known about different business family attributes with the appropriate family science theories, our hope is to accelerate efforts to understand the myriad ways business families shape family businesses.